GAMBARAN TUNA DAKSA YANG BEKERJA - Merdiasi, Danella (Noetic Psychology, 2017)
Abstract. This study described the point of view of the disabled person that have been experienced in the field of employment. There were difficulties that have been experienced of disabled person when they were looking for a job as in terms of accessibility, limited opportunity to work in the field of formal and informal sectors, and low public awareness and acceptance of work on disabled world. The purpose of this research was to find a picture of optimism disabled in the line of work. Optimism is an individuals belief that a bad event or failure does not preclude individuals to keep working reach the goal. This study used a qualitative approach with a case study using data collection methods such as interview. The participants in this study were two disabled people who used wheelchairs and had experience difficulty in finding employment. The results of this study showed both participants had an optimistic attitude, even if they had different views.Keywords: disabled people, job, optimism